(untitled) - Moore, G.E. (Cambridge, 1984)
It took us thousands of years of struggling with science and ethics before we thought to combine the two. While scientific ethics has advanced only gradually, the science of ethics burst into existence in 1903 with the publication of G.E. Moore's Principia Ethica, which did for the study of morality what Whitehead and Russell's Principia Mathematica did for mathematics--clarify old confusions and define terms that are still with us today. Practically overnight, ethicists turned into meta-ethicists, studying their own terms to establish theoretical ground on which to stand before trying to build any prescriptive edifices.
Keywords: Ethics